OS10.4 Intrathecal liposomal cytarabine plus systemic therapy versus systemic chemotherapy alone for leptomeningeal metastasis from breast cancer - a randomized study. Final results. (6th September 2019) - Le Rhun, E; Wallet, J; Mailliez, A; Le Deley, M; Rodrigues, I; Boulanger, T; Lorgis, V; Barriere, J; Robin, Y; Weller, M; Bonneterre, J
Abstract: BACKGROUND: Leptomeningeal metastasis (LM) is a common manifestation in metastatic breast cancer. Standards of care remain controversial, notably intrathecal pharmacotherapy. MATERIAL AND METHODS: DEPO-SEIN was a randomized open-label phase III study to explore the addition of intrathecal liposomal cytarabine to systemic therapy for the treatment of newly diagnosed LM from breast cancer. Patients diagnosed with LM based on the detection of tumor cells in the cerebrospinal fluid or typical clinical and neuroimaging signs of LM were randomly assigned to receive systemic therapy alone (control group) or systemic therapy plus intrathecal liposomal cytarabine (five injections of 50 mg every two weeks, followed by one monthly injection of 50 mg until progression, unacceptable toxicity or for one year) (experimental group). Progression-free survival related to LM (LM-PFS) was the primary endpoint. RESULTS: Thirty-seven and 36 patients were assigned to the control and the experimental groups. The median number of liposomal cytarabine injections in the experimental group was five (range 1–20). Focal radiotherapy was performed in six patients (16%) and three patients (8%) in the control and experimental groups. In the intent-to-treat population, median LM-PFS was 2·2 months (95% confidence interval (CI) 1·3-3·1) in the control versus 3·8 months (95% CI 2·3–6·8) in the experimental group (hazard ratio 0·61, 95% CI 0·38-0·98) (p=0·04). Seventy-one patients have died. Median OS was 4·0 months (95% CI 2·2–6·3) in the control versus 7·3 months (95% CI 3·9-9·6) in the experimental group (hazard ratio 0·85, 95% CI 0·53-1·36) (p=0·51). Serious adverse events were reported in 22 and 30 patients in the control and experimental groups. Quality of life until progression did not differ between groups. CONCLUSION: Intrathecal liposomal cytarabine improves LM-related PFS. A larger confirmatory trial with optimized patient selection criteria may be required to demonstrate a survival benefit from intrathecal pharmacotherapy.